Information overload : an international challenge to professional engineers and technical communicators - Strother, Judith B.; Ulijn, J. M.; Fazal, Zohra (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
"This book covers the ever-increasing problem of information overload from both the professional and academic perspectives. Focusing on the needs of practicing engineers and professional communicators, it addresses the causes and costs of information overload, along with strategies and techniques for reducing and minimizing its negative effects. The theoretical framework of information overload and ideas for future research are also presented. The book brings together an international group of authors, providing a truly global point of view on this important, rarely covered topic"--
Information Overload: An International Challenge to Professional Engineers and Technical Communicators -- Of, 24/7 Media, and Data Deluge: The Evolution of Information Overload Theories and Concepts -- The Challenge of Information Balance in the Age of Affluent Communication -- Information Shaman for Digital Tribes -- The Influence of Culture on Information Overload -- Effect of Color, Visual Form, and Textual Information on Information Overload -- Cost of Information Overload in End-User Documentation -- Technologies for Dealing with Information Overload: An Engineer's Point of View -- Blindfolded Through the Information Hurricane? A Review of a Manager's Strategy to Cope with the Information Paradox.
Includes bibliographical references.
Print version record.
Keywords: Information resources management; Time management; TECHNOLOGY & ENGINEERING -- Technical Writing; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Information resources management; Time management; Electronic books; Electronic books